Problems of Democratic and Dignified Election in Indonesian Simultaneously Electoral Era - Prasetio,; Karjoko, Lego; Addy Listya Wardhani, Lita Tyesta; Marwiyah, Siti; Rachmi Handayani, I Gusti Ayu Ketut; Jaelani, Abdul Kadir; Tahir, Ach.; Al-Fatih, Sholahuddin (International Journal of Criminology and Sociology, 2022)
This research was motivated by the section material in Act No. 7 of 2017 concerning General Election that not arranged in a structured, systematic and massive, so it appears the section material that overlaps with Constitutional Court and the Constitution of 1945. The purpose of this study is to analyze the problems of simultaneous elections in 2019 in order to bring democracy with dignity and integrity in the next election. The research type is a literature study. This research uses laws and conceptual approach. The main data of this study is obtained from primary and secondary law materials. The result showed that the problems in the section material of Electoral Lawimplicate to the practice, namely the chaos in updating of the voter list led to manipulation fraudulent of the voters list,10,520 polling stations had a shortage of election supplies, ballot boxes Voting Organizing Group received thatnot sealed as many as 6,474 polling stations, ballot papers that exchanged between Electoral District as many 3,411 Voting place and 527 Voting Organizing Group officer died and 11 239 sick.